Mammomonogamus laryngeus, Ryzhikov, 1948: A new Brazilian human case - Maria Donini Souza Dias, Rosa (1998)
Mammomonogamus laryngeus, Ryzhikov, 1948: A new brazilian human case. Mammomonogamus (Syngamus) laryngeus , commom parasite of upper respiratory tract at birds and mammals, unusually parasites the mano The new case of syngamosis in Brazil is described. The patient was a woman with a history of persistent and chronic cough and by bronchoscopy was removed two parasites, a couple, that were identified as M. laryngeus. Rev. Inst. Adolfo Lutz, 57 (2):55-58, 1998.